The regulatory effects of monocytes on human natural killer cells activated by lipopolysaccharides - Lindemann, R A (Journal of periodontal research, 1991)
Lipopolysaccharides (LPS) rapidly enhance cytotoxicity of human natural killer (NK) cells against tumor targets. The regulatory effects of peripheral blood monocytes (MO) on this activation were measured. When lymphocytes were kept at a constant number in culture containing LPS from oral and enteric bacteria, increasing the percentage of MO caused a dose-dependent suppression of NK cytotoxicity. This suppression was reversed by adding the prostaglandin (PG) inhibitor indomethacin which indicates that PGE was released by MO stimulated by LPS. PGE is known to suppress NK activity by its effects on cAMP. MO separated from lymphocytes by transwell membranes also suppressed NK cells in the presence of LPS but this action was again reversed by indomethacin. This suggests that cell-to-cell contact is not necessary for MO to suppress NK cytotoxicity when stimulated by LPS. The role of interleukin-1 (IL-1) and tumor necrosis factor (TNF) in NK suppression was studied. Antibodies to IL-1 and TNF did not alter the suppression mediated by MO on NK activity. Adding IL-1 or TNF to cell cultures without MO or LPS had no effect on NK activity after 24 h. TNF, but not IL-1, enhanced NK activity in the presence of LPS in cultures without MO. When PGE was preincubated with only lymphocytes for 2 h, the activating effects of a secondary stimulation, interleukin-2 (IL-2), were inhibited. IL-1 had no effect on IL-2 activation when pre-incubated with PBL but TNF slightly enhanced IL-2-induced NK cytotoxicity.